The designer's dictionary of color - Adams, Sean; Helfand, Jessica (New York, NY Abrams, 2017)
The Designer's Dictionary of Colour provides an in-depth look at 30 colours key to art and graphic design. Organized by spectrum, in colour-by-colour sections for easy navigation, this book documents each hue with charts showing colour range and palette variations
1 10
Keywords: Color; Color guides; Color in design; Design; Design; Design; Farbe; Farm life -- England -- Fiction; Color; Color guides; Color in design